Geomorphological Characteristics of the Italian Side of Canin Massif (Julian Alps) using Digital Terrain Analysis and Field Observations - Telbisz, Tamás; Mari, László; Szabó, Lénárd (Acta Carsologica, 2011)
In this paper, by the example of Canin Massif, it is demonstrated, how GIS-techniques can be used for the study of high mountain karst terrains. In case of Canin, elevation and slope histograms show characteristic differences in plateau levels and landforming processes between the northern, western and southern sectors of the mountains. Ridge and valley map (derived from the digital elevation model) and thalweg analysis are used to recognize drainage reorganizations north of the Italian Canin plateau. Potential snow accumulation locations and nunataks are determined based mainly on the slope map. Geomorphological sketch maps and statistical analysis of closed depressions are also carried out in this study supporting the relatively young age of superficial karstification and the strong structural impact. Finally, it is concluded, that quantitative and visual capabilities of GIS are useful in discriminating the effects of glacial, fluvial, structural and karst processes.